Intrahepatic CD161hiCD8+T Cell Recruitment Has a Pathogenetic Potential in Chronic HBV Infection - Jianfei Li; Qian Liu; Wanlu Duan; Zhi Duan; Futing Liu; Mengqi Ruan; Qiyin Zong; Hao Zhang; Qiang Zhou; Qin Wang (Immunity, Inflammation and Disease)
ABSTRACT Backgrounds and Aims CD8+T cells are crucially associated with the fight against hepatitis B virus (HBV) infection. CD161 has been shown to express remarkably on HCV‐specific CD8+T cells. However, the accurate function of CD161+CD8+T cells in HBV immunity or pathogenesis remains undetermined. Methods Blood samples were collected from 25 chronic hepatitis B (CHB) patients. Peripheral blood levels of CD161+CD8+T cells and their correlation with serum ALT levels were analyzed in CHB patients. To analyze the in vivo CD161+CD8+T cell's number, function, and intrahepatic recruitment characteristics, HBV replication mouse models were established. The expression of CD161 on HBV‐specific CD8+T cells was also detected by analyzing CD161+CD8+T cell functions during infection. Results Patients with CHB infection had a markedly lower peripheral blood frequency of CD161+CD8+T cells than did healthy controls and negatively correlated with serum ALT level. Furthermore, compared to the control mice, the frequency of CD161+CD8+T cells was significantly decreased in the blood of acute and chronic HBV‐replicating mice. Moreover, CHB‐replicating mice had significantly increased hepatic levels of CD161+CD8+T cells, which was not observed in the acute group of mice. Additionally, the CD161+CD8+T cells were categorized into CD161hi and CD161intCD8+T cells and it was revealed that in the liver of CHB‐replicating mice the primary recruited cells were CD161hiCD8+T. Intrahepatic CD161hiCD8+T cells demonstrated increased CXCR6 expression, enhanced production of cytokine IL‐17 and TNF‐ɑ, and reduced IFN‐γ secretion. Accordingly, the CXCL16 mRNA expression in the liver tissue of CHB‐replication mice was markedly higher than in acute HBV‐replicating and control mice. The study also revealed that HBV‐specific CD8+T cells were mainly CD161‐CD8+T cells. Conclusion During HBV infection, the intrahepatic recruitment of CD161+CD8+T cells was mainly CD161hiCD8+T cell subpopulation, which has a weak antiviral response, but increased pro‐inflammatory effect, suggesting that CD161 may serve as a potential marker of liver‐damaging T cells.